Oscillator regularity of the trap activation energies in NaCl crystals - Gumenjuk, A.F.; Kutovyi, S.Yu.; Kurilova, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The energy spectra of traps in NaCl crystals were studied in detail by the method of thermoluminescence. Crystals of NaCl were undoped but treated thermally in different ways. The activation energies of traps form a single oscillator series, En= ћwTL(n+1/2), ћwTL=903 cm⁻¹. Contrary to the other previously studied crystals having the complicated lattices, in Raman spectra of NaCl the corresponding line ћwRam= ћwTL was not found. It is assumed that the oscillator regularity is governed by the polaron nature of traps. The trap activation energy is determined by a vibration level from which a transition of a charge carrier to an excited luminescence center becomes possible and depends on a distance between these centers.